Surfactant proteins of the human larynx - Sheats, Michelle; Schröder, Henrik; Rauscha, F.; Bohr, Christopher; Kißlinger, Franziska; De Tristan, J.; Iro, Heinrich; Garreis, Fabian; Paulsen, Friedrich; Schicht, Martin; Bräuer, Lars (Annals of Anatomy-Anatomischer Anzeiger, 2016)
PURPOSE: Surfactant proteins (SPs) originally identified in lung tissue are important players in the innate immune system. Beyond this, they contribute to stability and rheology of gaseous or aqueous interphases. In the present study, we determined the expression and presence of SPs (A, B, C and D) in different areas of the human larynx. METHODS: mRNA expression of SP-A, -B, -C and -D was analyzed by means of RT-PCR in healthy samples of epiglottis, vocal and vestibular folds, subglottis and trachea. Distribution and localization of all four SPs were analyzed by Western blot and immunohistochemistry in healthy human tissue samples. RESULTS: All four SPs were detected at the mRNA- and protein level in the human larynx as well as by means of immunohistochemistry in the different tissue samples of the human larynx. CONCLUSION: The results reveal that all four SPs are produced with different expression patterns within the human larynx. Based on the known functions, our results suggest that SPs might be involved in maintaining mucus rheology and subsequently they could be essential components for proper phonation. Moreover, the proteins seem to play a role in immune defense of the larynx.
EVALuna2:33358